Broader autism phenotype in mothers predicts social responsiveness in young children with autism spectrum disorders. Issue 3 (14th July 2014) - Hasegawa, Chiaki; Kikuchi, Mitsuru; Yoshimura, Yuko; Hiraishi, Hirotoshi; Munesue, Toshio; Nakatani, Hideo; Higashida, Haruhiro; Asada, Minoru; Oi, Manabu; Minabe, Yoshio
<x xml:space="preserve">Abstract</x> Aims The aim of this study was to identify phenotypes in mothers and fathers that are specifically associated with disturbances in reciprocal social interactions and communication in their young children with autism spectrum disorder (ASD) in a Japanese sample. Methods Autistic traits in parents were evaluated using the Autism‐spectrum Quotient (AQ), the Empathy Quotient (EQ) and the Systemizing Quotient (SQ) in 88 parents (44 mothers and corresponding fathers) of children with ASD and in 60 parents (30 mothers and corresponding fathers) of typically developing (TD) children. For the measurement of autistic traits in children, we employed the Social Responsiveness Scale (SRS). Results In two of the five AQ subscales (social skills and communication), the parents of ASD children scored significantly higher than did the parents of TD children, regardless of whether the parent was a mother or a father. In addition, in mothers of ASD children, there were significant positive correlations between two of the five AQ subscales (attention‐switching and communication) and the SRS T‐score in their children. Conclusions This is the first study to demonstrate that the social skills and communication subscales in the AQ are more sensitive as autism traits in a Japanese sample and to demonstrate that some autistic traits in mothers are specifically associated with disturbances in the social ability of their young children with ASD, as measured by the SRS score. Further study is necessary to determine whether these results were caused by genetic or environmental factors.